2020
DOI: 10.1159/000507639
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Psychosocial Problems of Medical Health Workers during the COVID-19 Epidemic in China

Abstract: Objective: We explored whether medical health workers had more psychosocial problems than nonmedical health workers during the COVID-19 outbreak. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

131
1,414
38
137

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 1,394 publications
(1,720 citation statements)
references
References 20 publications
131
1,414
38
137
Order By: Relevance
“…However, this is not the way the analysis is conducted (see above). majority were German-speaking (n = 1124, 79.7%), women (n = 934, 66.2%), had a median age of 34 years [ [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] and median professional experience of 10 years [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Median working hours in the sample was 45 [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this is not the way the analysis is conducted (see above). majority were German-speaking (n = 1124, 79.7%), women (n = 934, 66.2%), had a median age of 34 years [ [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] and median professional experience of 10 years [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Median working hours in the sample was 45 [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]…”
Section: Resultsmentioning
confidence: 99%
“…19 In a third Chinese study conducted between the end of February and the beginning of March, Zhang et al reported that 927 medical HCWs had a higher prevalence of insomnia, anxiety, depression, somatization, and obsessive-compulsives symptoms than 1255 non-medical HCWs. 20 Furthermore, being a woman was a significant predictor of insomnia, anxiety, and depression, and exposure to patients was a predictor of anxiety and insomnia. 20 However, a study among 470 HCWs in Singapore undertaken during the same period of time found the opposite, namely lower levels of stress-related symptoms in medical compared to non-medical HCWs.…”
Section: Several Studies Conductedmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results agree with past research demonstrating that working at home or working without restrictions when compared to not working was associated with better mental health, life satisfaction and lower distress in Chinese individuals during the COVID-19 pandemic (S. X. . On the other hand, healthcare workers presented elevated values of insomnia/poor sleep quality, fear, anxiety, depression, and OC symptoms due to COVID-19 (Huang and Zhao, 2020;Lu et al, 2020;W.-R. Zhang et al, 2020). Thus, further analyses should explore the effect of riskier job categories on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare workers at higher risk of exposure to the virus experience a greater psychological impact than those with less exposure (e.g., [10]: SARS). In China, frontline healthcare workers caring directly for patients with COVID-19 experienced stress, anxiety and insomnia, and exhibited higher levels of severe mental health symptoms than those in secondary roles [13][14][15]. Conversely, other studies have shown a higher prevalence of psychological distress among non-frontline staff, possibly due to these workers having less access to information and psychological support [16].…”
Section: Introductionmentioning
confidence: 99%